The First Alkaline-Earth Azidoaurate(III), Ba[Au(N3)4]2 • 4 H2O - Subasi, Yaprak; Tekin, Elif Sena; Prots, Yurii; Jach, Franziska; Somer, Mehmet; Afyon, Semih; Hoehn, Peter (Wiley-V C H Verlag Gmbh, 2023)
Transparent, dark orange Ba[Au(N-3)(4)](2) center dot 4 H2O was synthesized by reaction of Ba(N-3)(2) and AuCl3 or HAuCl4 in aqueous solution. The novel barium tetraazidoaurate(III) tetrahydrate crystallizes in the monoclinic space group Cc (no. 9) with a=1813.68(17) pm, b=1737.95(11) pm, c=682.04(8) pm and beta=108.849(4)degrees. The predominant structural features of Ba[Au(N-3)(4)](2) center dot 4 H2O are two crystallographically independent discrete anions [Au(N-3)(4)](-) with gold in a tetragonal planar coordination by nitrogen. Vibrational spectra show good agreement with those of other azidoaurates(III). Upon drying, this salt was shown to be a highly explosive material.
Keywords: alkaline-earth metals; azides; crystal structures; gold; vibrational spectroscopy